Discrete polygonal supramolecular architectures of isocytosine-based Pt(ii) complexes at the solution/graphite interface. Issue 74 (25th August 2016) - El Garah, Mohamed; Sinn, Stephan; Dianat, Arezoo; Santana-Bonilla, Alejandro; Gutierrez, Rafael; De Cola, Luisa; Cuniberti, Gianaurelio; Ciesielski, Artur; Samorì, Paolo
Abstract : Polygonal supramolecular architectures of a Pt(ii ) complex including trimers, tetramers, pentamers and hexamers were self-assembled via hydrogen bonding between isocytosine moieties. Abstract : Polygonal supramolecular architectures of a Pt(ii ) complex including trimers, tetramers, pentamers and hexamers were self-assembled via hydrogen bonding between isocytosine moieties; their structure at the solid/liquid interface was unravelled by in situ scanning tunneling microscopy imaging. Density functional theory calculations provided in-depth insight into the thermodynamics of their formation by exploring the different energy contributions attributed to the molecular self-assembly and adsorption processes.